(untitled) (International Journal of Islamic Business, 2019)
Minimal research to date has examined whether and how corruption and diversification influence the asset quality of Islamic banks from the agency perspective. The study aims to fill this research gap using a sample of 155 banks (28 Islamic banks and 127 conventional banks) in three Asian countries (Indonesia, Malaysia, and Pakistan) from 2006 to 2012. Estimation of the dynamic panel data model reveals that corruption negatively affects the asset quality of Islamic banks whereas conventional banks see no such effect. Corruption also proves to strengthen (weaken) any negative (positive) effect of diversification on the asset quality of Islamic banks, in particular. Furthermore, the modifying effect of corruption is particularly found in more corrupt countries (Indonesia and Pakistan) as opposed to a less corrupt country (Malaysia). Overall, results suggest that banks should engage in diversification moderately because diversification’s negative effect can overpower its positive effect. In addition, Islamic banks and particularly small ones should watch out for the negative effect of corruption because these banks’ asset quality is more influenced by corruption than other banks. Furthermore, it is crucial for policymakers to effectively control corruption to maximize the asset quality of banks for better financial stability of the banking sector. This is especially true for Islamic banks because they are more likely to incur higher agency costs as opposed to conventional banks.